THE IMPACT OF FACILITIES, SERVICE QUALITY AND THE ROLE OF SOCIAL MEDIA ON TOURISTS INTERESTED IN RETURNING WITH SATISFACTION AS A MEDIATOR (STUDY ON 17 ISLAND NATURAL TOURISM PARKS IN RIUNG DISTRICT, NGADA DISTRICT) - Yohanes Ronaldo Dheo Rato; Simon Sia Niha; Anggraeny Paridy (Jurnal Ekonomi, 2023)
This research aims to determine the influence of facilities, service quality and the role of social media partially on interest in repeat visits, the influence of facilities, quality of service and the role of social media partially on tourist satisfaction, the influence of tourist satisfaction on interested in returning, and tourist satisfaction mediates the influence of facilities , tourist satisfaction, and the role of social media on interested in returning on 17 island natural tourism parks in Riung District. This type of research is quantitative research. The sampling technique used was non-probability using the accidental sampling method with a sample of 90 respondents and data collection through questionnaires. The data analysis technique in this research is descriptive statistics and inferential statistics using Smart PLS version 3.0 software. The results of the analysis show that Facilities (X1), Social Media (X3),  has a positive and significant effect on interested in returning, Service Quality (X2) and Satisfaction (Z) has  insignificant effect on interested in returning. Facilities (X1) and  Social Media (X3) has a positive and significant effect on Satisfaction (Z). Tourist satisfaction is able to mediate the influence of facilities, service quality and social media on interested in returning.